The characterization of stem cells from human exfoliated deciduous teeth using trypsin enzym - Tri Wijayanti Puspitasari (Fakultas Kedokteran Gigi Universitas Airlangga, 2014)
Background: Now a days, treatment in dentistry, using tissue regeneration that based on the stem cells from human exfoliated deciduous teeth (SHED), grows rapidly. For several reason, the isolated and cultured SHED is difficult to be applied in Indonesia, therefore the modification is needed. This difficulties were caused by the pulp anatomy, the heterogeneous populations in the pulp chamber and the limitations of tools and materials at the laboratory. Purpose: This research was aimed to examine that the modifications of isolation and culture technique of SHEDs for characterization by using the marker of CD105. Methods: The research was experimental laboratory with the cross sectional design. The samples were the human exfoliated deciduous teeth from the children patients of Pediatric Dentistry Department of Universitas Airlangga Dental Hospital which matched the criteria. Dental pulps were isolated and cultured by using the modifications of Trypsin enzymes. Results: The healthy SHEDs could be produced from the modifications of isolation and culture and positively shown the expression of marker CD105 which were indicated by the fluorencent microscope. Conclusion: SHED which isolated and cultured by using the modified techniques, positively characterized by using marker CD105.